1982
DOI: 10.1139/g82-078
|View full text |Cite
|
Sign up to set email alerts
|

WHITE FLOWER COLOR IN RAPE (BRASSICA NAPUS) ASSOCIATED WITH A RADISH (RAPHANUS SATIVUS) CHROMOSOME

Abstract: The inheritance of flower color was investigated in progeny from crosses between a normal, yellow flowering rape strain (Brassica napus L.) and a white flowering strain developed at the University of Manitoba by backcrossing the white flower color from Raphanobrassica into B. napus. The chromosome number of all yellow flowering plants examined was normal (2n = 38), whereas all white flowering plants examined contained a single or a pair of small radish (Raphanus sativus L.) chromosomes each carrying a dominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

1985
1985
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 1 publication
0
4
0
1
Order By: Relevance
“…Presence of alien chromosomes in B. napus has also been observed by Sernyk and Stefansson ( 1982). A pair of Raphanus sativus chromosomes were responsible for a white flower characteristic in B. napus.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Presence of alien chromosomes in B. napus has also been observed by Sernyk and Stefansson ( 1982). A pair of Raphanus sativus chromosomes were responsible for a white flower characteristic in B. napus.…”
Section: Resultsmentioning
confidence: 77%
“…Heterosis for seed yield in hybrid rapeseed (Brassica napus) has been reported by various authors (Sernyk and Stefansson 1983;Buson 1980;Guan 1980;Schuster and Michael 1976;Shiga 1976). Hybrids have shown a 20-40% increase in seed production over their midparents or standard cultivars.…”
Section: Introductionmentioning
confidence: 88%
“…3C, F and Table 4). Kato and Tokumasu (1976) reported that a single dominant gene controlled white petal color in radish, and Sernyk and Stefansson (1982) reported that the B. napus strain added with a R. sativus chromosome developed at University of Manitoba produced white flowers. Therefore, it was assumed that a single dominant gene determining white petal color was located on the g-chromosome of radish.…”
Section: Transmission Rate Of the Added Radish Chromosomementioning
confidence: 99%
“…Sources of rapeseed petal colour variation mainly include natural variation, artificial chemical mutagenesis and transfer from Brassica oleracea . Zhang et al (2007) identified natural mutants of rapeseed with golden yellow petals; Li et al (2001) identified orange‐red petal mutants in cytoplasmic male sterility lines; Sernyk and Stefansson (1982) hybridized white‐flowered B. oleracea with rapeseed to obtain white petal mutant material (2 n = 40). However, the mechanism of petal colour regulation in rapeseed is not fully understood.…”
Section: Introductionmentioning
confidence: 99%